Use of Risk Scoring System in Upper Gastrointestinal Haemorrhage: A Critical Review - Abdul Rahiem Ahmed, Yasar Albushra (مجلة الجزيرة للعلوم الصحية; مجلد 8 عدد 2 (2012), 2012)
Upper gastrointestinal bleeding (UGIB) represents a substantial clinical and economic burden with significant mortality and morbidity. Validated prognostic scales are used to stratify patients into low and high risk, on the basis of clinical, laboratory, and endoscopic criteria. Early identiﬁcation of high-risk patients allows appropriate intervention, which minimizes morbidity and mortality.